Thermal stability of ultrathin and high dielectric ta‐C films coated with Ag nanostructures for SERS. (23rd November 2017) - Yan, Bo; Li, Ke; Gu, Ping; Li, Zhen; Tang, Chaojun; Liu, Fanxin; Zhan, Peng; Sui, Chenghua; Wang, Zhenlin
Abstract: Surface‐enhanced Raman spectroscopy (SERS) becomes one of the most desirable analytical techniques in the field of molecule detection. In some case, SERS needs to be performed at high temperature, for example, in catalytic reaction, in which dielectric film‐coated Ag nanostructures have been developed as extremely stable SERS substrates. Here, we study the thermal stability in air for a 1‐nm tetrahedral amorphous carbon (ta‐C) film‐coated Ag nanostructure and its application in SERS. The result indicates that the 1‐nm ta‐C can preserve its mechanical properties and has good thermal stability at the temperature below 300 °C. However, under heating above 300 °C, its sp 3 (diamond structure) content has an apparent decrease so that the 1‐nm ta‐C film cannot protect Ag‐based SERS substrates. The further SERS experiments demonstrate that the 1‐nm ta‐C‐coated Ag substrate can maintain its enhancement capability after heating below 300 °C by comparing to the substrate without heating, with further heating above 300 °C eventually leading to a loss of SERS capability, which is consistent with the study of ta‐C's thermal stability. We expected that our method could extend the potential applications of SERS in investigation of high‐temperature chemical reactions. Abstract : We study the thermal stability in air for the 1‐nm tetrahedral amorphous carbon (ta‐C) film‐coated Ag nanostructure and its application in surface‐enhanced Raman spectroscopy (SERS). The result indicates that 1‐nm ta‐C can preserve its mechanical properties at the temperature below 300 °C. Further SERS experiments demonstrate that 1‐nm ta‐C‐coated Ag substrate can maintain its enhancement capability after heating below 300 °C.